2019
DOI: 10.1016/j.sjbs.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional nano-catalyzed pyrolyzates from branch of Cinnamomum camphora

Abstract: Cinnamomum camphora is an excellent tree species for construction of forest construction of Henan Province, China. The diverse bioactive components of nano-catalyzed pyrolyzates form cold-acclimated C. camphora branch (CCB) in North China were explored. The raw powder of CCB treated with nano-catalyst (Ag, NiO, 1/2Ag + 1/2NiO) were pyrolyzed at two temperatures (550 °C and 700 °C), respectively. The main pyrolyzates are bioactive components of bioenergy, biomedicines, food additive, spices, cosmetics and chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Tetradecanol, 66 a colorless solid at normal temperature, is the main raw material for the production of sodium fourteen alkyl polyoxyethylene ether succinic acid mono sulfonic acid and fourteen alkyl polyoxypropylene succinic acid mono sulfonic acid sodium, which can be used as the raw material for organic synthesis and surfactants and can also be used as food additive and spice. Hexadecanol, 26,67 A white leaf‐like crystalline substance can be used in the manufacture of spices, 68 cosmetics, detergents, plasticizers, and so on 69 . It is used as a matrix in all kinds of cosmetics 70 and is especially suitable for ointment acid and emulsion.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Tetradecanol, 66 a colorless solid at normal temperature, is the main raw material for the production of sodium fourteen alkyl polyoxyethylene ether succinic acid mono sulfonic acid and fourteen alkyl polyoxypropylene succinic acid mono sulfonic acid sodium, which can be used as the raw material for organic synthesis and surfactants and can also be used as food additive and spice. Hexadecanol, 26,67 A white leaf‐like crystalline substance can be used in the manufacture of spices, 68 cosmetics, detergents, plasticizers, and so on 69 . It is used as a matrix in all kinds of cosmetics 70 and is especially suitable for ointment acid and emulsion.…”
Section: Results and Analysismentioning
confidence: 99%
“…The fresh pitaya pulp and pericarp were separated, and the pericarp and pulp were weighed and basically controlled within the range of 100 g + 5 g 23 . For the pulp, pour the ethanol with 1:5 ratio into the pulp and then use the blender to crush it and reserve it 24–26 . The pericarp of pitaya is crushed by BX484 type pulverizer, and the ethanol with material to liquid ratio of 1:5 is added 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that quercetin can reduce apoptosis induced by hypoxia and rescue phosphorylation of AMPK [15]. Beta-sitosterol has antipyretic, analgesic, anti-inflammatory, and antioxidant functions and plays roles in cough and phlegm elimination, immune regulation and tissue repair [16,17]. Stigmasterol is present in the membrane [18] and has anti-inflammatory effects [19].…”
Section: Discussionmentioning
confidence: 99%
“…Their leaves are especially rich in volatile oil components, including monoterpenes, sesquiterpenes and diterpenes (Hou et al, 2020;Tian et al, 2021). Camphor tree has high medicinal, ornamental, ecological and economic value Liu et al, 2019;Zhang et al, 2020). As a TCM, C. camphora can be used to treat rheumatism and arthralgia, sores and swelling, skin itching, poisonous insect bites, etc.…”
Section: Introductionmentioning
confidence: 99%